Digitalisation of state and municipal services, using the federal state information system “Unified Population Register” as an example - S. S. Belikova; A. V. Belikov (Вестник университета)
The article formulates the prerequisites that prompted state authorities to implement the project of the federal state information system “Unified Population Register” in order to promptly obtain the most complete and reliable information on the citizens of the Russian Federation. The results of an overview of changes for citizens and government agencies from the introduction of a population information system have been presented. The relevance of the project has been analysed and the pros and cons have been considered. The creation of a single population register will simplify interdepartmental cooperation, facilitate the provision of e-services and social assistance to the population, help to combat crime more effectively, and further develop the information society.